The social route to mental health: A systematic review and synthesis of theories linking social relationships to mental health to inform interventions - Lærke Mai Bonde Andersen; Amanda Nikolajew Rasmussen; Nicola J. Reavley; Henrik Bøggild; Charlotte Overgaard (SSM - Mental Health, 2021)
Interventions that support social relationships are widely used to promote mental health and increasingly involve the use of digital technologies. Solid theoretical underpinning is crucial for interventions to achieve the intended outcomes and avoid unintended consequences. Several theories linking social relationships to mental health exist in the literature but plurality and overlapping elements complicate the choice of appropriate theory. The aim of this study was to systematically review and synthesize theories linking social relationships to mental health to extract key theoretical assumptions to explain 1) how social relationships influence mental health, and 2) the circumstances that distinguish beneficial social relationships from relationships that have no effects or cause harm. Results of the synthesis are discussed in relation to general interventions, and implications for the use of digital interventions as novel tools to support social relationships and mental health are drawn out. The systematic search was performed in five electronic databases: PubMed, Sociological Abstracts, PsycINFO, CINAHL, and Embase. Six theoretical frameworks met our inclusion criteria and were included in the synthesis. The theory synthesis followed three stages: 1. synthesis preparation, 2. synthesis, and 3. synthesis refinement. Findings show that various social relationships influence people's mental health, both in adverse situations and in those without adversities. Their impact is shaped by a complex interplay of individual and relational circumstances and the individual's subjective perceptions. Quality and content are central to separating beneficial relationships from those that are not beneficial. Findings support the potential of interventions based on social relationships to improve mental health but highlight the need to consider the circumstances where relationships might do more harm than good. Digital interventions may improve people's opportunities to develop new relationships or strengthen existing ones, but they require a special focus on ensuring the quality and content of relationships to maximize this potential benefit.